Devolution and public perceptions and experience of health services in Pakistan: linked cross sectional surveys in 2002 and 2004 - Ansari Umaira; Cockcroft Anne; Omer Khalid; Ansari Noor MD; Khan Amir; Chaudhry Ubaid; Andersson Neil (BMC, 2011)
Abstract Background The government of Pakistan introduced devolution in 2001. Responsibility for delivery of most health services passed from provincial to district governments. Two national surveys examined public opinions, use, and experience of health services in 2001 and 2004, to assess the impact of devolution on these services from the point of view of the public. Methods A stratified random cluster sample drawn in 2001 and revisited in 2004 included households in all districts. Field teams administered a questionnaire covering views about available health services, use of government and private health services, and experience and satisfaction with the service. Focus groups in each community discussed reasons behind the findings, and district nazims (elected mayors) and administrators commented about implementation of devolution. Multivariate analysis, with an adjustment for clustering, examined changes over time, and associations with use and satisfaction with services in 2004. Results Few of 57,321 households interviewed in 2002 were satisfied with available government health services (23%), with a similar satisfaction (27%) among 53,960 households in 2004. Less households used government health services in 2004 (24%) than in 2002 (29%); the decrease was significant in the most populous province. In 2004, households were more likely to use government services if they were satisfied with the services, poorer, or less educated. The majority of users of government health services were satisfied; the increase from 63% to 67% between 2002 and 2004 was significant in two provinces. Satisfaction in 2004 was higher among users of private services (87%) or private unqualified practitioners (78%). Users of government services who received all medicines from the facility or who were given an explanation of their condition were more likely to be satisfied. Focus groups explained that people avoid government health services particularly because of bad treatment from staff, and unavailable or poor quality medicines. District nazims and administrators cited problems with implementation of devolution, especially with transfer of funds. Conclusions Under devolution, the public did not experience improved government health services, but devolution was not fully implemented as intended. An ongoing social audit process could provide a basis for local and national accountability of health services.